1989
DOI: 10.4319/lo.1989.34.1.0001
|View full text |Cite
|
Sign up to set email alerts
|

Particle transport in lakes: Models and measurements

Abstract: Rest&s of experimental measurements and mathematical modeling demonstrate that coagulation in lakes can be sufficiently rapid and extensive to affect suspended particle concentrations and sedimenting fluxes significantly. The process dominates particle removal in Lake Ziirich and substantially influences particle concentrations in the water column of Lake Sempach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(84 citation statements)
references
References 19 publications
2
82
0
Order By: Relevance
“…Particle aggregation is a ubiquitous phenomenon (Weilenmann et al 1989), which complicates the light-scattering effects of the involved particles (Boss et al 2009b). This effect is much more prominent in the high-divalent-cationconcentration environments of marine waters, particularly in coastal waters (Bowers et al 2011;Hill et al 2011;Neukermans et al 2012), compared with the much lower divalent cation levels of freshwaters (Peng and Effler 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Particle aggregation is a ubiquitous phenomenon (Weilenmann et al 1989), which complicates the light-scattering effects of the involved particles (Boss et al 2009b). This effect is much more prominent in the high-divalent-cationconcentration environments of marine waters, particularly in coastal waters (Bowers et al 2011;Hill et al 2011;Neukermans et al 2012), compared with the much lower divalent cation levels of freshwaters (Peng and Effler 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the POM sinking flux with regard to its size distribution in lakes have shown that, as in marine systems, larger particles contribute more to the sinking flux than smaller ones (Stabel 1985, Bloesch & Burgi 1989, Weilenmann et al 1989. Aggregation increases particle size and thus settling velocity, accelerates particle removal, and reduces particle concentrations in the water column (Eisma 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This 61% decrease in S was accompanied by a 65% decrease in [Ca 2ϩ ] . The high [Ca 2ϩ ] promoted coagulation (Weilenmann et al 1989) and thus increased deposition losses of particles (including phytoplankton) from the trophogenic layers . The downward flux of particulate organic carbon (POC df , g m…”
mentioning
confidence: 99%